Biogas production from fermented sugarcane vinasse: impact of trace elements supplementation - Arruda, Beatriz G.; Costa, Rachel B. [UNESP]; Zaiat, Marcelo; Braga, Adriana F. M. (Springer Nature, 2025)
The anaerobic digestion of the sugarcane vinasse from ethanol production can generate bioenergy and reduce its polluting potential. However, the biogas production efficiency might be hampered by trace elements (TE) seasonal variation and unbalanced composition in the vinasse. This study evaluated the effect of TE supplementation, i.e. Co, Cu, Fe, Mn, Ni, and Se, on the maximum CH4 production (P), the maximum CH4 production rate (Rm) and the maximum productivity (Pr) from sugarcane fermented vinasse from a two-stage AD system. Fractional Factorial Design (FFD) was applied to screen TE with positive effects on the responses, and Central Composite Design (CCD) was used to optimise these responses, followed by a validation test. Co, Ni and Mn positive effects were identified for the considered responses using FFD. As Ni significantly positively affected P and Pr in CCD, it was added at the concentration of 0.9 mg L-1 in the validation test. The Ni supplementation was responsible for a 50% increase in the Rm response, it improved the Pr by 17% and decreased the peak time by 29% compared to the control condition. The decreasing concentrations of acetic acid (HAc) and COD during the assays suggest that the Ni supplementation might have stimulated CODH/ACS, an enzyme involved in the consumption of HAc by acetoclastic methanogens.
Keywords: Anaerobic digestion; Design of experiments; Methane production; Micronutrients; Sugar and alcohol industry wastewater